Pemberdayaan Kelompok Tani Domba Desa Megulung Kidul Berbasis Syariah untuk Meningkatkan Kesejahteraan Ekonomi - Mugiarto, Mugiarto (Abdibaraya, 2025)
This study aims to examine the effectiveness of economic empowerment for sheep farmers in Megulung Kidul Village using a shariah-based approach. Qualitative research methods were employed to collect data through interviews, observations, and document analysis. The results indicate that shariah-based empowerment enhances farmers' economic well-being through increased production, income, and quality of life. Successful empowerment strategies include technical training, mentoring, and effective product marketing